The Role of Village Communities in Preserving Forests in the Negeri Saunulu, Tehoru District, Central Maluku Regency - Nova S. Tuwael; Jusmy D. Putuhena; Billy B Seipalla (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to explore the role of village communities in preserving forests in the Negeri Saunulu, Tehoru District, Central Maluku Regency. The method used in this study is a qualitative method using descriptive analysis. Data collection techniques are interviews, focus group discussions, observation, and documentation. Sampling is done by simple random method. With a sample of 10% of the total 301 heads of families, 35 heads of families in in the Negeri Saunulu. Respondents in this study are religious leaders, traditional leaders, youth leaders, women leaders, and village communities. Data analysis is inductive or qualitative analysis results emphasize meaning rather than generalization. The results of the study show the role of village communities in preserving forests in the Negeri Saunulu, Tehoru District, Central Maluku Regency through reforestation and plant maintenance.